Exploring Magical Realism And Cultural Significance In Neil Gaiman’s The Ocean At The End Of The Lane - Fefti Ayu Hariyani (Fakultas Ilmu Budaya, 2024)
The Ocean at the End of the Lane by Neil Gaiman, first published in 2013, tells the story of an unnamed man who visits his childhood home and remembers about his experiences with Lettie Hempstock, a young girl from the nearby farmhouse where she lives with her mother and grandmother. Lettie leads him on extraordinary adventures out of the ordinary, encountering magical creatures and facing dangerous supernatural threats. These happen because the suicide of an opal miner has brought a supernatural creature into their world. The Hempstocks, especially Lettie's grandmother, protect them from these dark forces. The novel explores magical realism through Wendy B. Faris's five key elements, analyzing how these elements shape Gaiman's narrative. The magical elements challenge characters' perceptions of reality, seamlessly blending with everyday life and creating a sense of uncertainty that blurs the line between reality and imagination. Gaiman portrays the phenomenal world, grounding these magical elements in a tangible setting while disrupting conventional ideas of time, space, and identity, reshaping the narrator's journey. This research analyzes The Ocean at the End of the Lane by Neil Gaiman through a postmodern perspective to examine its cultural significance. The researcher employs postmodernism as the overarching theory, viewing elements within the novel as reflective of postmodern themes and concepts. Qualitative research methods are utilized to explore narrative data from the novel and related sources, focusing on how Gaiman employs magical realism to challenge conventional narratives. The analysis deconstructs the novel to identify key elements of magical realism, such as irreducible elements, the phenomenal world, unsettling doubts, merging of realms, and disruption of time, space, and identity. These elements are examined through the lens of postmodern theories, particularly Jean-François Lyotard's fragmentation of grand narratives and Brian McHale's ontological pluralism. The study aims to highlight how Gaiman's narrative style embraces multiple realities and perspectives, emphasizing localized, personal stories over universal truths.
Reupload Repositori File 10 Februari 2026_Kholif Basri
Keywords: phenomenal world; unsettling doubts; and disruption of time